Impact of pregnancy/childbirth on dispositional optimism in the context of risk of depression, mental health status and satisfaction with life - Kułak-Bejda, Agnieszka; Shpakou, Andrei; Khvoryk, Natallia; Hutsikava, Liudmila; Aydin Avci, Ilknur; Eren, Dilek Celik; Kourkouta, Lambrini; Tsaloglidou, Areti; Koukourikos, Konstantinos; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2024)
Introduction: Life optimism is an inseparable element accompanying every human being. It takes different values depending on the life situation. The present study aimed to measure the level of dispositional optimism in postpartum and pregnant women, compared to women who are not pregnant and have never given birth in Poland, Greece, Turkey, Belarus, and Russia, depending on the level of life satisfaction, risk of depression and mental health. Material and methods: A case-control study was carried out among 2017 women, including 584 pregnant women, 528 postpartum women, and 906 women who had never been pregnant and had never given birth (control group) from Poland, Greece, Turkey, Belarus, and Russia. The study used the LOT-R Life Orientation Test, the Beck Depression Scale (BDI), the Satisfaction With Life Scale (SWLS), the GHQ- 28, and the Edinburgh Postnatal Depression Scale (EPDS) - only in the postpartum group. Results: Women from the control group showed an average level of optimism, obtaining an average of 16 points in Belarus, 13.4 points in Poland, 13.3 points in Greece, 13.5 points in Turkey, and Russia - 16.3 points. Pregnant women from Belarus had a high level of optimism (17 points), and in other countries, an average level of optimism was in Poland - 14.5 points, Greece - 14.0 points, Turkey - 14.3 points, and Russia - 16.5 points. Women after childbirth had a high level of optimism in Belarus (17.4 points) and Russia (17.2 points), and in other countries had the average level of optimism. In these countries, the lowest level of optimism was found in non-pregnant women. No significant correlation between age and life optimism was found in any group. In Poland, life optimism increased with age in women who had never been pregnant, and in Turkey, in women who were pregnant and after childbirth. Conclusions: Pregnant women from Belarus had a higher level of optimism than other countries. Non-pregnant women had an average level of optimism. Future studies should include larger groups of women and consider other factors that may additionally contribute to dispositional optimism